Impact of Urban Heat Island on Formation of Precipitation in Indian Western Coastal Cities - Patil, Rachana; Surawar, Meenal (Alanya Üniversitesi, 2023)
Rapid urbanization is leading to a drastic hike in anthropogenic activities and urban surface alterations. As a result, there are many repercussions, one of them being higher temperatures in urban areas when compared to rural areas. This phenomenon is termed Urban Heat Island (UHI). The impacts of urban surface characteristics, climate, and population density on UHI have been extensively studied. However, the influence of UHI on the local climate remains elusive. Relatively few studies demonstrate interrelation between UHI, population density, and unanticipated precipitation events. Therefore, it is important to comprehend the connection as it can impact extreme temperature events like heat waves and unanticipated precipitation events like flash flooding. The objective of this study is to investigate the association between UHI, population density, and precipitation in the summer and winter seasons in Indian Western Coastal Cities. To comprehend this association, a hypothesis test employing the Spearman rank correlation coefficient is conducted for 1991, 2001, 2011, and 2021. From the study, it is found that in summer, the surface temperature is directly proportional to population density and inversely proportional to precipitation. In winter the contrary relation is observed. This study also provides the seasonal variation and temporal evolution of the correlation among the parameters. This research will aid in making informed decisions for urban planning and addressing climate change.